ASSESSMENT OF ROUTINE IMMUNIZATION PROGRAM AT PRIMARY HEALTH CENTRE LEVEL IN JAMNAGAR DISTRICT - Sanghavi, Mithun M (National Journal of Medical Research, 2013)
Background: PHC is a key place for implementing routine immunization program and storing of vaccines. Present study conducted to assess various components of routine immunization program at PHC level. This study also identifies key strengths, weaknesses, opportunities and threats at PHC level for implementing Routine Immunization Program. Materials and Methods: A cross-sectional facility based study was conducted in Jamnagar district from March 2010 to March 2012. Total two Primary Health Centers were randomly selected from each 07 block offices in Jamnagar District. So, total 14 PHCs were included in the study representing 40% of total PHCs in the district. Data were collected by structured Routine Immunization check list for PHC/CHC developed by WHO/Government of India. Results: 78.57% PHCs did not prepare Dropout chart. 42.86% of PHCs did not have their map. Frost > 5mm seen in 78.57% of PHCs. DF temperature did not between -15 to -25’C in 28.57% PHCs. Voltage stabilizer was not functional in 14.29% PHCs. Temperature Log book was not properly maintained in more than half of PHCs. 35.71% PHCs suffer of shortage of one or more vaccines. Data discrepancy of stock was observed in 57.14%. No AEFI reported in all PHCs in the previous 03 months. Supervision found to poor in majority of PHCs. Conclusions: Various issues regarding immunization program at PHC level like planning, cold chain maintenance, vaccine stocks, supervision etc. should be properly addressed for improving the quality of immunization services in the district.